Analysis of Student Self-Regulated Learning and Creative Thinking Through the Project-Based Learning Model on Renewable Energy Topics - Ratih Windyaningsiwi; Sunyoto Eko Nugroho; Bambang Subali (Universitas Negeri Semarang, 2025)
Self-regulated learning is essential for students to be proactive in their learning, and creative thinking is crucial for overcoming challenges and generating innovative solutions. Project-Based Learning (PjBL) has been proposed as an effective method for teaching subjects such as renewable energy, allowing students to apply concepts in a real-world context. However, challenges persist in implementing PjBL, including student adaptation and lack of structured materials. This study aims to assess the impact of the PjBL model on students' self-regulated learning and creative thinking, identify factors that promote self-regulated learning, and understand barriers to developing creative thinking. Conducted at SMA Negeri 11 Sarolangun, this study involved two experimental classes and one control class. Using a mixed-method approach with a sequential explanatory design, this research employed a quasi-experimental method with a non-equivalent control group design. Data were collected using questionnaires, creative thinking tests, and interviews, and analyzed using parametric statistical tests and qualitative descriptive analysis. The results showed that PjBL had a significant positive impact on self-regulated learning and creative thinking, with a supportive learning environment being a key factor. The t-test results showed a significant effect on self-regulated learning (0.002) and creative thinking (0.04), both below the 0.05 threshold. Effect size analysis indicated a high impact on self-regulated learning and moderate impact on creative thinking variable.